Pathogenicity and antibiotic resistance analysis of Vibrio species found in coastal water at mainly beach of Shenzhen, China - Huang, Ziwei; Anokyewaa, Melody Abena; Wang, Junlin; Jian, Jichang; Lu, Yishan (Frontiers in Marine Science, 2022)
Offshore industries and resources are the links between humans and the marine ecosystem. Several risk factors are associated with beach activities. The risk of Vibrio infection at bathing beaches is often overlooked as there are virtually no regulations regarding them. In this study, we investigated the current prevalence of pathogenic Vibrio spp. on the main beaches of Shenzhen. The risk indicator levels of pathogenic Vibrio species obtained were analyzed using 17 virulence genes mainly associated with Vibrio species and are responsible for several ailments and infections. A total of 60 Vibrio strains were isolated and identified by morphological observation, evolutionary tree alignment, and biochemical testing. There was a high abundance of Vibrio in the seawater. Also, a positive correlation was observed between the presence of virulence genes and the exhibition of high pathogenicity after artificially infecting fish with some of the virulent Vibrio species. In the infection experiment, it was observed that all the zebrafish infected with MEDF7 (Vibrio alginolyticus) and JSW-YELLOW (Vibrio harveyi) died a day after injection, with varying degrees of abdominal enlargement and skin ulceration. The mortality rates for strains with medium risk and low risk were 65% and 45%, respectively. Lethal dose 50 (LD50) values were 5.67 ×104 CFU/fish, 3.72 ×105 CFU/fish, and 4.31 ×105 CFU/fish for the high-risk, medium-risk, and low-risk strains of zebrafish, respectively. The results of the antibiotic sensitivity test showed that all the six experimental strains, except JSW-YELLOW, were resistant to doxycycline and neopenicillin. In summary, our study first identified and evaluated the pathogenicity of Vibrio in the Shenzhen beach baths, serving as a scientific benchmark for Vibrio risk prevention and control as well as guidance for Vibrio diagnosis through virulence factor detection and risk classification.